Сбалансированность региональных бюджетов в условиях макроэкономической неопределенности (на примере окружного бюджета ЯНАО) : BALANCE OF REGIONAL BUDGETS IN CONDITIONS OF MACROECONOMIC UNCERTAINTY (ON THE EXAMPLE OF THE DISTRICT BUDGET OF YAMAL-NENETS AUTONOMOUS DISTRICT) - Е. А. Гончарова (Экономика и бизнес: теория и практика, 2018)
В статье рассматривается сбалансированность регионального бюджета в условиях макроэкономической нестабильности. Проведен анализ состава и динамики доходов и расходов бюджета субъекта Российской Федерации на примере окружного бюджета Ямало-Ненецкого автономного округа. Выявлены основные факторы, влияющие на сбалансированность окружного бюджета Ямало-Ненецкого автономного округа, сформулированы рекомендации по повышению его бюджетной устойчивости и сбалансированности. : The article discusses the process of forming a regional budget in conditions of macroeconomic instability. The analysis of composition and dynamics of incomes and expenditures of the regional budget on the example of the regional budget of the Yamal-Nenets Autonomous District was conducted. The main factors influencing the balance of the regional budget were identified. The author gave recommendations on improving the budget sustainability and balance of the regional budget of the Yamal-Nenets Autonomous District.